Indonesia’s Digital Transformation: How E-Government is Revolutionizing Public Services - Abdurrahman, Muhammad; Suherman, Dadang; Bhimasena, Abhiram; Carlos, Frederick Martin (Indonesia Discourse, 2025)
This study investigates Indonesia’s ongoing digital transformation, with a particular focus on the role of e-government in revolutionizing public services. As the country navigates a rapidly evolving digital landscape, e-government initiatives have emerged as crucial tools for enhancing public sector efficiency, improving citizen engagement, and promoting transparency. The research examines the implementation of various e-government programs, such as digitalized administrative services, online public service platforms, and electronic governance systems, assessing their impact on service delivery and the accessibility of government services to the public. This research reveals that while significant progress has been made, including greater convenience for citizens and improved administrative efficiency, challenges persist, including issues related to digital infrastructure, cybersecurity concerns, and disparities in access to technology between urban and rural areas. The novelty of this research lies in its evaluation of both the technological advancements and the socio-political factors that influence the success of e-government initiatives in Indonesia. The urgency of this study is highlighted by the increasing dependence on digital tools in governance, which has been further accelerated by the COVID-19 pandemic. This research contributes to the broader discussion on e-government by offering recommendations for improving digital infrastructure, addressing the digital divide, and ensuring that e-government reforms are inclusive and sustainable in Indonesia’s diverse socio-economic context.